PENGARUH MUROTAL AL QUR’AN TERHADAP KECEMASAN PASIEN PRE OPERASI BEDAH ORTHOPEDI - Maulana, Reza '; Elita, Veny '; ', Misrawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this research was to determine the effect of murotal Al Qur’an toward anxiety level in patient with pre orthopedic surgery. The research used quasy experimental with non equivalent control-group was divided into experimental group and control group in Arifin Achmad Hospital. Sample of this research was 40 people. With 20 people as the experimental group and 20 people as a control group by using purposive techniques sampling. Instruments of this research was State-Traite Anxiety Index (STAI) which has been tested for the validity and reability. The experimental group were given interventions with murotal Al Qur’an one time in one day for 10 minutes. The data analyzed by using univariate with normality test and frequences. Bivariate analyzed using dependent t-test and independent t-test. The result of the research showed that there was a decrease anxiety level in experimental group with 29 score and increase of anxiety level in control group with 0,30 score and statistic analyze of showed there was significant level of anxiety index after giving intervention of experimental group with p value= 0,000 < α (0,05). The conclusion is murotal Al Qur’an influence the level anxiety of the patient. The result is expected of murotal Al Qur’an to be one of nursing intervention to decrease anxiety level in patient with orthopedic surgery. Key words: Anxiety, murotal Al Qur’an, orthopedic